The Resolution of the Problem of Evil in the Works of Àyatullah Jawadi Àmuli - Muslim Muhammadi (حکمت اسرا, 2010)
The ontological and epistemological roots of evil and the relevance of the problem to the divine essence, attributes and acts, has always warranted the attention of thinkers and intellectuals. Hence the field of theodicy and the continuous efforts of philosophers and theologians to defend the principle of divine justice by responding to the objections at hand. ÀyatullÁh JawÁdi Àmuli approaches the problem of evil in a comprehensive way that is based upon the QurÁn, rational demonstration, and mysticism. He expounds on the nature of evil—making a distinction between the practical resolution of the problem and the philosophical causes of evil—and goes on to present two practical resolutions (evil as privation, and the ‘best order’ argument). The present study looks into how this problem is dealt with in the works of the ÀyatullÁh.